Mesoporous titanium carbonitride derived from mesoporous C3N5 for highly efficient hydrogen evolution reaction. (15th August 2022) - Gujral, Harpreet Singh; Singh, Gurwinder; Yang, Jae Hun; Sathish, C.I.; Yi, Jiabao; Karakoti, Ajay; Fawaz, Mohammed; Ramadass, Kavitha; Al-Muhtaseb, Ala'a H.; Yu, Xiaojiang; Breese, Mark B.H.; Vinu, Ajayan
Abstract: Transition metal nitrides have gained a lot of attention as they have a significant potential for the electrocatalytic applications owing to their unique structure and electrical properties. However, the synthesis of mesoporous metal nitrides without compromising their electronic conductivity and the porous features is quite challenging. Herein, we demonstrate an integrated strategy of combining reactive templating approach and the doping for the synthesis of highly crystalline and mesoporous titanium carbonitride (MTiCN) materials through a simple heat treatment of the mixture of titanium tetrachloride and mesoporous C3 N5 via reactive templating approach. The synthesized MTiCN materials possess rod shape morphology, high specific surface area, and mesoporous structure together with the highly graphic carbon matrix which are inherited from the mesoporous C3 N5 . The optimized MTiCN exhibits considerable electrocatalytic hydrogen evolution reaction (HER) activity with a low onset potential of 37.6 mV vs RHE and Tafel slope of 34 mV.dec −1 which lies very close to the commercial platinum/carbon. This work would offer a simple solution for the rational design of series of porous transition metal carbon nitrides with excellent electrocatalytic properties using carbon nitrides with tunable nitrogen and carbon contents for electrochemical conversion and storage applications. Graphical abstract: Image 1 Highlights: Mesoporous TiCN is synthesized using the reactive templating and carbon doping. Mesoporous TiCN exhibits high specific surface area and high crystallinity. N and C content in mesoporous TiCN can be tuned by varying the amount of C3 N5 . HER performance of mesoporous TiCN is similar to that of commercial Pt/C.